Intradermal injection of an anti‐Langerin‐HIVGag fusion vaccine targets epidermal Langerhans cells in nonhuman primates and can be tracked in vivo. Issue 3 (19th January 2016) - Salabert, Nina; Todorova, Biliana; Martinon, Frédéric; Boisgard, Raphaël; Zurawski, Gerard; Zurawski, Sandra; Dereuddre‐Bosquet, Nathalie; Cosma, Antonio; Kortulewski, Thierry; Banchereau, Jacques; Levy, Yves; Le Grand, Roger; et al.
Abstract : We characterized by fluorescence imaging the dynamics of early local events following the intradermal injection of a vaccine‐targeted Langerhans cells (LC) and resiquimod (R‐848) in nonhuman primates. Anti‐Langerin‐HIVGag vaccine specifically targets epidermal LC and the co‐injection of R848 stimulates the recruitment of HLA‐DR+ inflammatory cells to the skina. Abstract : The development of new immunization strategies requires a better understanding of early molecular and cellular events occurring at the site of injection. The skin is particularly rich in immune cells and represents an attractive site for vaccine administration. Here, we specifically targeted vaccine antigens to epidermal Langerhans cells (LCs) using a fusion protein composed of HIV antigens and a monoclonal antibody targeting Langerin. We developed a fluorescence imaging approach to visualize, in vivo, the vaccine‐targeted cells. Studies were performed in nonhuman primates (NHPs) because of their relevance as a model to assess human vaccines. We directly demonstrated that in NHPs, intradermally injected anti‐Langerin‐HIVGag specifically targets epidermal LCs and induces rapid changes in the LC network, including LC activation and migration out of the epidermis. Vaccine targeting of LCs significantly improved anti‐HIV immune response without requirement of an adjuvant. Although the co‐injection of the TLR‐7/8 synthetic ligand, R‐848 (resiquimod), with the vaccine, did not enhance significantly the antibody response, it stimulated recruitment of HLA‐DR+ inflammatory cells to the site of immunization. This study allowed us to characterize the dynamics of early local events following the injection of a vaccine‐targeted epidermal LCs and R‐848.